The Role of Pathogenic Staphylococci in the Occurrence of Purulent-Inflammatory Complications and the Specifics of Their Bacteriological Diagnosis - Shokhsanam, Ruzieva (Journal of Innovation in Education and Social Research, 2025)
Purulent - inflammatory diseases today's on the day medicine current from problems one are, they are from the operation next period, as well as various traumas and immunity weakening with related in cases wide Staphylococci not only purulent - inflammatory processes instigator microorganisms as, maybe they to antibiotics endurance level clinical with in practice serious problems brought Especially MRSA (Methicillin- resistant Staphylococcus aureus) resistant Staphylococcus aureus) strains spread staphylococci against the fight further is making it difficult.